Bioactivity Diversity (Antibacterial and Antioxidant) of Macroalgae in the Ekas Beach Area, Lombok - Nurul Furqan, Baiq Repika; Yamin, Imam Syahputra; Umami, Sri Sofiati (Universitas Islam Negeri Mataram, 2024)
Macroalgae in the southern coastal area of Lombok has not been explored much in terms of bioactivity. The aim of this research is to explore the usefulness of 9 types of macroalgae on Ekas Lombok beach by searching for their bioactivity capabilities, whether each macroalgae has no bioactivity at all, has antibacterial and antioxidant activity, only has antibacterial activity but no antioxidant activity or vice versa and whether there are macroalgae that even have anticancer activity. The method used in this research consists of several steps: Macroalgae Sampling, Morphological Analysis of Macroalgae Samples, Isolation of active compounds from macroalgae and Cytotoxic Test on Breast Cancer Cells in Vitro which consists of 3 tests: Culture and sub culture of MCF-7 Breast Cancer Cells, Cell Viability and Cytotoxicity Test with MTT and DNA Isolation of MCF-7 Breast Cancer Cells. The research results show that the macroalgae with the best antibacterial activity is the red macroalgae Acanthophora spicifera and the macroalgae with the best antioxidant activity is the green macroalgae Ulva reticulata.